Seroprevalence of Zika virus and dengue virus infections in migrants in Italy - Frasca, Federica; Romani, Francesco Eugenio; Gentilini Cacciola, Elio; Colavita, Francesca; Palermo, Enrico; Maddaloni, Luca; Rosa, Luigi; D’Auria, Alessandra; Baccolini, Valentina; Migliara, Giuseppe; Matusali, Giulia; Ceccarelli, Giancarlo; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionEstimating the burden of Zika virus (ZIKV) and dengue virus (DENV) infections in migrants is important to promote their health status and recommend appropriate interventions. We aimed to estimate the seroprevalence of ZIKV and DENV in migrants from high endemic countries attended at a referral center in Rome (Italy), arriving via the Mediterranean from North and sub-Saharan Africa and South-East Asia.MethodsSixty-four serum samples from migrants were tested for anti-ZIKV and anti-DENV immunoglobulin (Ig) G and IgM by ELISA. Serum samples with detectable Ig were analyzed by indirect immunofluorescence assay (IFA). For confirmatory testing and given the cross-reactivity of antibodies between orthoflaviviruses, all positive IFA sera were tested by virus neutralization test. ZIKV and DENV RNA were assessed by RT Real-Time PCR. ResultsAll serum samples were negative for anti-ZIKV IgG, while 12.50% (n=8/64) were positive for anti-ZIKV IgM by ELISA. IFA showed that only 1 of 8 serum samples (12.50%) was positive for anti-ZIKV IgM, but ZIKV RNA was undetectable. The seroprevalence of anti-DENV IgG by ELISA was 59.37% (n=38/64), mostly confirmed by IFA (97.36%, n=37/38). Furthermore, anti-DENV IgM were detected in 9 serum samples (n=9/64, 14.06%) by ELISA, previously tested negative for anti-DENV IgG. Of these, 2 sera were confirmed by IFA, but DENV RNA was not detectable. Anti-DENV neutralizing antibodies (nAbs) were detected in 27% of anti-DENV IgG sera (n=10/37) tested by IFA. Multiple linear regression analysis showed that sub-Saharan African origin was an independent factor for the development of anti-DENV nAbs (p=0.009), while age and gender had no effect. Sera negatives for anti-DENV nAbs but with detectable anti-DENV IgG tested by IFA had nAbs to another orthoflavivirus (n=25/27, 92.59%) such as West Nile virus (WNV) (n=17/25, 68%), Yellow fever virus (YFV) (n=7/25, 28%) and Usutu virus (USUV) (n=1/25, 4%). DiscussionA high prevalence of anti-orthoflavivirus IgG, especially against DENV, was found in the migrant population studied, but no infections were detected. With the recent outbreaks of autochthonous DENV infections in Italy, the risk of secondary DENV infection - and severe disease – could be high. Robust serological surveillance, vaccination and prevention strategies for this vulnerable group are needed.